Chelation Motifs Affecting Metal-dependent Viral Enzymes: N′-acylhydrazone Ligands as Dual Target Inhibitors of HIV-1 Integrase and Reverse Transcriptase Ribonuclease H Domain - Carcelli, Mauro; Rogolino, Dominga; Gatti, Anna; Pala, Nicolino; Corona, Angela; Caredda, Alessia; Tramontano, Enzo; Pannecouque, Christophe; Naesens, Lieve; Esposito, Francesca (Frontiers in Microbiology, 2017)
Human immunodeficiency virus type 1 (HIV-1) infection, still represent a serious global health emergency. The chronic toxicity derived from the current anti-retroviral therapy limits the prolonged use of several antiretroviral agents, continuously requiring the discovery of new antiviral agents with innovative strategies of action. In particular, the development of single molecules targeting two proteins (dual inhibitors) is one of the current main goals in drug discovery. In this contest, metal-chelating molecules have been extensively explored as potential inhibitors of viral metal-dependent enzymes, resulting in some important classes of antiviral agents. Inhibition of HIV Integrase (IN) is, in this sense, paradigmatic. HIV-1 IN and Reverse Transcriptase-associated Ribonuclease H (RNase H) active sites show structural homologies, with the presence of two Mg(II) cofactors, hence it seems possible to inhibit both enzymes by means of chelating ligands with analogous structural features. Here we present a series of N’-acylhydrazone ligands with groups able to chelate the Mg(II) hard Lewis acid ions in the active sites of both the enzymes, resulting in dual inhibitors with micromolar and even nanomolar activities. The most interesting identified N’-acylhydrazone analog, compound 18, shows dual RNase H-IN inhibition and it is also able to inhibit viral replication in cell-based antiviral assays in the low micromolar range. Computational modeling studies were also conducted to explore the binding attitudes of some model ligands within the active site of both the enzymes.